2017
DOI: 10.5815/ijitcs.2017.09.03
|View full text |Cite
|
Sign up to set email alerts
|

Towards Automated Web Accessibility Evaluation: A Comparative Study

Abstract: Abstract-With each passing day, the Web is becoming increasingly important in our lives. Hence, the need of making it more accessible to everyone, especially for the disabled and elderly spurred a great interest in automated tools, the total registered number of which has been continuously increasing and reached from forty-five software bids in 2014 to ninety-three in 2017. The purpose of this empirical research is to assess and compare eight popular and free online automated Web accessibility evaluation tools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 33 publications
0
8
0
2
Order By: Relevance
“…The checkers have been compared, validated, and described in detail in previous research (Abduganiev, 2017;Ismail et al, 2018). It is well-established that multiple checkers should be used when researching accessibility of webpages (Timbi-Sisalima et al, 2016).…”
Section: Checker Selectionmentioning
confidence: 99%
“…The checkers have been compared, validated, and described in detail in previous research (Abduganiev, 2017;Ismail et al, 2018). It is well-established that multiple checkers should be used when researching accessibility of webpages (Timbi-Sisalima et al, 2016).…”
Section: Checker Selectionmentioning
confidence: 99%
“…Mas, apesar dessas limitações, sua utilização ainda é válida e pode ajudar na melhoria do nível de acessibilidade das páginas avaliadas. É aconselhável utilizar mais de uma ferramenta para que elas se complementem (uma ferramenta pode cobrir um ponto falho da outra) [Abduganiev 2017].…”
Section: Wai-ariaunclassified
“…Por causa de sua importância no processo de criação dos web sites, advinda da velocidade proporcionada na identificação de erros de acessibilidade, os avaliadores automáticos continuam a ser estudados pela comunidade científica, e novas ferramentas continuam a ser desenvolvidas [Abduganiev 2017]. Há ainda ferramentas desenvolvidas com recursos de inteligência artificial para que cada vez mais verificações possam ser feitas automaticamente [Alsaeedi 2020].…”
Section: Wai-ariaunclassified
“…Overall, a solution to Web accessibility assessment, comprehensive of all the possible useful features is still lacking. Investigations of accessibility evaluation tools conducted in the past have actually pointed out various issues [ 2 , 4 , 6 8 ]. They already revealed that such tools should provide more support for developers in conducting accessibility audits as well as in understanding and fixing errors.…”
Section: State Of the Art In Guidelines And Automatic Tools For Web Amentioning
confidence: 99%